Agile xue xi shou ce Scrum, XP, jing shi he kan ban fang fa = Learning Agile / = Learning Agile - Stellman, Andrew; Greene, Jennifer 1971- (GoTop Information, Inc., 2015)
Detailed summary in vernacular field.